DESCRIPTION OF DIETS OF THE 12-36-MONTH-OLD CHILDREN RESIDING IN MOSCOW - I. M. Guseva; T. E. Borovik; A. V. Surzhik; L. S. Namazova-Baranova; I. N. Zakharova; N. G. Zvonkova; N. N. Semenova; O. L. Lukoyanova; T. V. Bushueva; T. N. Stepanova (Педиатрическая фармакология)
Significance. Imbalanced diet in early childhood often results in medical issues, including mental retardation, impaired adaptation mechanisms and worsened immunological protection. The amount of studies, which could help to assess dietary peculiarities of 1-3-year-old children living in a Russian megalopolis and reveal probable deficiencies of the essential macro- and micronutrients, as well as the prevalence of eating behavior disorders. The study was aimed at assessing the nature and peculiarities of the diet of the 12-35-month-old children residing in Moscow. Patients and methods. 106 1-3-year-old children were examined at two pediatric polyclinics in Moscow; they were divided into two groups: I – 12-23-month-old children, II – 24‑35-month-old children. Results. The authors performed a comprehensive analysis of actual diets of young children, including assessment of the nature of consumed foods and dishes, as well as of nutritional value of daily rations. Conclusions. The authors established that diets of most 1‑3‑year-old children residing in the megalopolis conform to the current criteria. Excessive consumption of high-protein foods, insufficient consumption of specialized functional foods, early introduction of “adult foods” and non-observance of the dietary pattern were observed in several cases.